2010
DOI: 10.1007/s00402-010-1128-x
|View full text |Cite
|
Sign up to set email alerts
|

Revision surgery after trapeziometacarpal arthroplasty

Abstract: The overall results were assessed according to the Conolly score. The revision rate after primary arthroplasty at our institution was 2.9%. Most common problems for secondary surgery included mechanical pain due to crepitation of the base of the first metacarpal bone, neuropathy of the superficial branch of the radial nerve and concomitant scaphotrapezial arthritis. A total of 19 procedures were performed resulting in two good, five fair and five poor results. A treatment algorithm is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 18 publications
3
43
2
4
Order By: Relevance
“…Anatomical studies have shown that the FRC tendon passes near the volar surfaces of the scaphoid and trapezium in an osteofibrous groove [30,31]. Adhesion of the FCR tendon to residual bone fragments after the surgery may be the source of the tendinopathy [32]. These anatomical and functional relationships explain why FRC tendinopathy occurs with STT osteoarthritis [33][34][35].…”
Section: Tendinopathymentioning
confidence: 99%
“…Anatomical studies have shown that the FRC tendon passes near the volar surfaces of the scaphoid and trapezium in an osteofibrous groove [30,31]. Adhesion of the FCR tendon to residual bone fragments after the surgery may be the source of the tendinopathy [32]. These anatomical and functional relationships explain why FRC tendinopathy occurs with STT osteoarthritis [33][34][35].…”
Section: Tendinopathymentioning
confidence: 99%
“…Характерными осложнениями первичной артропластики седловидного сустава являются сохранение коллапса первого луча, несостоятельность или потеря фиксации восстановленных связок, подвывих, лизис интерпозиционного материала, распространение дегенеративного процесса на пястно-фаланговый и ладьевиднотрапециевидный суставы. клиническими проявлениями, как правило, служат сохранение боли или функциональная несостоятельность оперированного сустава [66]. повторные вмешательства ос-ложнены отсутствием пластического материала для восстановления высоты сустава и его стабилизации.…”
Section: ревизионная хирургия седловидного суставаunclassified
“…с их помощью легко восстанавливалась высота сустава, который стабилизировался за счет лигаментопластики. Этому методу часто отдавали предпочтение при неудачном протезировании -ножка спейсера заполняла дефект ткани пястной кости [33,66]. но анализ отдаленных результатов показал высокую частоту фрагментации имплантатов и реакции параартикулярных тканей, вызванных контактом с силиконом [52,66,67].…”
Section: ревизионная хирургия седловидного суставаunclassified
“…Ein dauerhaft unbefriedigendes Ergebnis mit Schmerzen und Funktionsstörungen im ersten Strahl ist selten. Megerle und Mitarbeiter beschrieben im eigenen Patientengut nach Ar throplastik auf Grundlage einer Rhizarthrose 2,9 % revisionsbe dürftige Komplikationen [20]. Die Proximalisierung des ersten Strahls ist eine der möglichen, unerwünschten Folgen der alleinigen Trapezektomie [1][2][3][4][5].…”
Section: Diskussion ▼unclassified